Trichoteirotillomania. - Chieco, P. (European Journal of Pediatric Dermatology, 2017)
Trichotillomania is the most frequent non-spontaneous alopecia. According to the psychiatry texts (DSM-V -TR) trichotillomania is linked to a defective control of impulses and to the search for pleasant sensations. In the adult, who usually practices it secretly, trichotillomania is a psychosis; in the child, who practices it in front of every-one, trichotillomania has the meaning of a tic, therefore a minor importance. A meaning similar has trichoteiromania caused by violent scratching of the scalp and associated with inflammation. Exceptionally, trichotillomania and trichoteiromania can coexist as in our case. Trichotemnomania is a variant caused by cutting or shaving of the hair; as well as self-inflicted this variant can be caused by a third subject, usually a parent. Much more serious are forms of alopecia induced by bites - trichodaganomania - or associated with ingestion of the hair in tricobenzoar -.